Implementasi Program KKN Bidang Pendidikan Melalui Kegiatan Mengajar dan Pembuatan Pojok Baca di Desa Takaras Kecamatan Manuhing Kabupaten Gunung Mas - Khairudin, Rahmat; Elenchi; Amanda, Gladys; Habibah, Enjelika; Bagus Suryanatha, Ida (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) is a form of student service to the community that integrates elements of education, research, and community engagement. The KKN program in Takaras Village, Manuhing Sub-district, Gunung Mas Regency, focused on the education sector with two main activities: teaching at various school levels and establishing a Reading Corner (Pojok Baca) at SD Negeri Takaras. This program aimed to improve the quality of learning, develop students’ skills, and foster reading interest from an early age. The implementation was carried out through observation, planning, implementation, and evaluation stages. The results showed an increase in learning motivation, student participation, and literacy culture in schools, particularly after the Reading Corner was inaugurated. Overall, the program demonstrates that collaboration between students, teachers, and the community can have a positive impact on the development of education in rural areas.